The Brazilian beef supply chain and food security: a productive inputs view (Research, Society and Development, 2021)
The alignment of food production systems with the trends and demands of the world population plays an important global role. This study aims to discuss the convergence of trends related to the Brazilian beef cattle supply chain from a food security perspective. Therefore, it includes important reports on the future of this supply chain and its input production, taking on a qualitative approach to consider trends in animal health, genetics, nutrition, forage, and farm machinery in terms of the development of Brazilian agriculture and the future of food and agribusiness. From a managerial point of view, it was possible to provide information capable of leading to a sustainable understanding. Thus, a content analysis of the documents was carried out, coding them through the Sustainable Development Goals and categorizing them by taking into account the 2030 Agenda’s five Ps (people, planet, prosperity, peace, and partnerships). Along this line, the discussion highlights the themes of poverty and climate change, emphasizing them with regard to the categorization social aspects – the P of people). Future trends will require a workforce prepared to deal with the additional limitations that can arise with the use of new technologies as productivity increases.